Patterns of Use of Antihypertensive Drugs in Hypertensive Patients in the Outpatient Unit of the Kowel Health Center, Pamekasan Regency - Alrosyidi, Ach Faruk; Humaidi, Fauzan; Ayu Lokahita, Dyah (Universitas Airlangga, 2022)
Inappropriate use of drugs had a large and detrimental impact on the unit or healthcare institution for patients and the community. Therefore, it was necessary to select and use drugs appropriately, so that drug interventions could achieve their goals (patient healing) with minimal drug side effects. This study aimed to determine the pattern of use of antihypertensive drugs in patients with hypertension in the outpatient unit of Kowel Health Center, Pamekasan Regency. Samples were taken from medical records of hypertensive patients from January to May 2022, with a total sample of 75 patients. The research variables included the type of drug, dose, frequency, duration of use, side effects, drug interactions, and patient control routines. The most widely used single dose drug was the calcium antagonist amlodipine, in 46 patients (61.33%). The highest combination dose was found in calcium antagonist + ACE inhibitor, namely amlodipine and captopril, in 3 patients (4%).Keywords: Antihypertensive Drugs, Kowel Health Center, the Pattern of Use of Drugs